Functional brain changes using electroencephalography after a 24-week multidomain intervention program to prevent dementia - Park, Hee Kyung; Choi, Seong Hye; Kim, SeonMyeong; Park, Ukeob; Kang, Seung Wan; Jeong, Jee Hyang; Moon, So Young; Hong, Chang Hyung; Song, Hong-Sun; Chun, Buong-O; Lee, Sun Min; Choi, Muncheong; et al. (Frontiers in Aging Neuroscience, 2022)
Quantitative electroencephalography (QEEG) has proven useful in predicting the response to various treatments, but, until now, no study has investigated changes in functional connectivity using QEEG following a lifestyle intervention program. We aimed to investigate neurophysiological changes in QEEG after a 24-week multidomain lifestyle intervention program in the SoUth Korean study to PrEvent cognitive impaiRment and protect BRAIN health through lifestyle intervention in at-risk elderly people (SUPERBRAIN). Participants without dementia and with at least one modifiable dementia risk factor, aged 60–79 years, were randomly assigned to the facility-based multidomain intervention (FMI) (n = 51), the home-based multidomain intervention (HMI) (n = 51), and the control group (n = 50). The analysis of this study included data from 44, 49, and 34 participants who underwent EEG at baseline and at the end of the study in the FMI, HMI, and control groups, respectively. The spectrum power and power ratio of EEG were calculated. Source cortical current density and functional connectivity were estimated by standardized low-resolution brain electromagnetic tomography. Participants who received the intervention showed increases in the power of the beta1 and beta3 bands and in the imaginary part of coherence of the alpha1 band compared to the control group. Decreases in the characteristic path lengths of the alpha1 band in the right supramarginal gyrus and right rostral middle frontal cortex were observed in those who received the intervention. This study showed positive biological changes, including increased functional connectivity and higher global efficiency in QEEG after a multidomain lifestyle intervention. Clinical trial registration [https://clinicaltrials.gov/ct2/show/NCT03980392] identifier [NCT03980392].